2016
DOI: 10.5547/01956574.37.3.cwoo
|View full text |Cite
|
Sign up to set email alerts
|

What Moves the Ex Post Variable Profit of Natural-Gas-Fired Generation in California?

Abstract: We use a large California database of over 32,000 hourly observations in the 45month period of April 2010 through December 2013 to document the ex post variable profit effects of multiple fundamental drivers on natural-gas-fired electricity generation. These drivers are the natural-gas price, system loads, nuclear capacities available, hydro conditions, and renewable generation. We find that profits are reduced by increases in generation from nuclear plants and wind farms, and are increased by increases in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…However, a growing literature has assessed some of these impacts as expressed through past market outcomes from the U.S. (e.g., Maggio 2012;Woo et al 2011Woo et al , 2013Woo et al , 2014Woo, Horowitz, et al 2016;Gil and Lin 2013;; Jenkins 2017; Hogan and Pope 2017; Makovich and Richards 2017; DOE 2017; Bajwa and Cavicchi 2017; Haratyk 2017). 10,11 The Importance of Physical and Institutional Flexibility Many of the impacts described above are affected by the underlying physical and institutional flexibility of the electricity system (e.g., Cochran et al 2014;IEA 2011).…”
Section: Impacts Of Vre On Wholesale Power Pricesmentioning
confidence: 99%
“…However, a growing literature has assessed some of these impacts as expressed through past market outcomes from the U.S. (e.g., Maggio 2012;Woo et al 2011Woo et al , 2013Woo et al , 2014Woo, Horowitz, et al 2016;Gil and Lin 2013;; Jenkins 2017; Hogan and Pope 2017; Makovich and Richards 2017; DOE 2017; Bajwa and Cavicchi 2017; Haratyk 2017). 10,11 The Importance of Physical and Institutional Flexibility Many of the impacts described above are affected by the underlying physical and institutional flexibility of the electricity system (e.g., Cochran et al 2014;IEA 2011).…”
Section: Impacts Of Vre On Wholesale Power Pricesmentioning
confidence: 99%
“…2 See for example Clò, Cataldi, & Zoppoli, 2015;Cludius, Hermann, Matthes, & Graichen, 2014;Cutler, Boerema, MacGill, & Outhred, 2011;Ederer, 2015;Haas, Lettner, Auer, & Duic, 2013;Kyritsis, Andersson, & Serletis, 2017;Perez-Arriaga & Batlle, 2012;Sáenz de Miera, del Río González, & Vizcaíno, 2008;Sensfuß, Ragwitz, & Genoese, 2008a;Welisch, Ortner, & Resch, 2016;Würzburg, Labandeira, & Linares, 2013. 3 See for example Bajwa & Cavicchi, 2017;DOE, 2017;Gil & Lin, 2013;Haratyk, 2017;Hogan & Pope, 2017;Jenkins, 2017;Maggio, 2012;Makovich & Richards, 2017;Wiser et al, 2016;Woo et al, 2013Woo et al, , 2014Woo, Horowitz, Moore, & Pacheco, 2011;Woo, Horowitz, et al, 2016; Similar developments can be found increasingly in the United States as well. Wiser et al (2017) comprehensively review wholesale electricity price data of U.S. ISOs and find evidence of changed temporal and geographic price patterns in areas with high VRE penetrations.…”
Section: Evidence Of Vre-induced Price Changesmentioning
confidence: 91%
“…Consider a risk-neutral GT affiliated with a Genco that uses natural gas as the marginal fuel Zarnikau et al, 2019Zarnikau et al, , 2020. A GT's expected hourly per MWh procurement cost in the contract period is E(X h ) = μ Xh < μ Ph , where X h = min(P h , HR × G h ), where HR = marginal heat rate (MMBtu per MWh) of natural-gas-fired generation and G h = spot natural gas price ($/MMBtu) in hour h (Woo, Horowitz, et al, 2016). This is because a GT would procure from the wholesale market if the hourly wholesale market price P h is less than own-generation's hourly marginal fuel cost of HR × G h .…”
Section: A Gentailer's Optimal Fpomentioning
confidence: 99%